2009
DOI: 10.3945/ajcn.2008.26807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1 and 3 g cinnamon on gastric emptying, satiety, and postprandial blood glucose, insulin, glucose-dependent insulinotropic polypeptide, glucagon-like peptide 1, and ghrelin concentrations in healthy subjects

Abstract: Ingestion of 3 g cinnamon reduced postprandial serum insulin and increased GLP-1 concentrations without significantly affecting blood glucose, GIP, the ghrelin concentration, satiety, or GER in healthy subjects. The results indicate a relation between the amount of cinnamon consumed and the decrease in insulin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 35 publications
6
91
1
1
Order By: Relevance
“…Hlebowicz and coauthors performed two series study to test the diabetes prevention effect by adding different doses of cinnamon into rice pudding. The intake of six grams of cinnamon reduced postprandial blood glucose and delayed gastric emptying without affecting satiety (Hlebowicz et al, 2009). The large quantity of proanthocyanidins used resulted in strong astringency taste.…”
Section: Cinnamonmentioning
confidence: 99%
“…Hlebowicz and coauthors performed two series study to test the diabetes prevention effect by adding different doses of cinnamon into rice pudding. The intake of six grams of cinnamon reduced postprandial blood glucose and delayed gastric emptying without affecting satiety (Hlebowicz et al, 2009). The large quantity of proanthocyanidins used resulted in strong astringency taste.…”
Section: Cinnamonmentioning
confidence: 99%
“…Water soluble polyphenols isolated from cinnamon has been shown to have strong insulinenhancing activity on cultured fat cells in vitro, [42]. Also, when tested in healthy subjects, cinnamon (3 g) added to a rice pudding (300 g) was shown to reduce post prandial serum insulin, but not glucose, levels compared to a rice pudding without cinnamon [25]. It is impossible to draw any conclusions regarding the effects of the antocyanins and/or polyphenols present in the oat meal based fruit drinks (RFOMD, BFOMD, BBFOMD) in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies generally have shown a good correlation between glucose and insulin responses. Thus, studies with cereals [26], and certain fruits like mango, melon, pineapple, kiwi, apple and black grapes [19,27] indicate good agreement between GI and II. In contrast studies with oranges and apples [28] as well as juice from these fruits [3,29] were reported to display unexpectedly high insulin responses.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] Drie studies daarvan hadden een open-label studieopzet, waarbij onderzocht werd wat eenmalige inname van kaneel voor effecten zou hebben op de postprandiale glucosewaarden. 15,16,22 Eén studie was uitgevoerd in Groot-Brittannië bij 8 gezonde mannen. Dit was een enkelblind, placebogecontroleerd cross-overonderzoek, waarin deze mannen 3 gram kaneel innamen voor een periode van 14 dagen.…”
Section: -11unclassified